Thermal expansivities and compressibilities of hydrous phases in the system MgO-SiO2-H2O: Talc, phase A and 10-angstrom phase - Pawley, A; Redfern, S; Wood, B (1995)
We have measured the thermal expansivity of talc, Mg3Si4O10(OH)2, and phase A, Mg7Si2O8(OH)6, and the compressibility of talc, phase A and 10-Å phase, Mg3Si4O10(OH)2 · xH2O, using powder X-ray diffraction. The thermal expansivity of talc and phase A were measured at temperatures up to 810°C and 600° C, respectively. Volumes of both phases increase linearly with temperature, and can be described as follows: Talc: V/V0 = 1 + 2.15 (± 0.05) × 10-5 (T - 298), V0 = 136.52 (± 0.03) cm3 mol-1; Phase A: V/ V0 = 1 + 4.86 (± 0.18) × 10-5 (T - 298), V0 = 154.42 (± 0.09) cm3 mol-1. Compressibility measurements of talc, 10-Å phase and phase A were made at pressures up to 6.05, 8.52 and 9.85 GPa, respectively. Values of the isothermal bulk modulus K298 and its pressure derivative K′, obtained by fitting the compressibility data to the Murnaghan equation, are as follows: Talc: K298 = 41.6 ± 0.9 GPa, K′ = 6.5 ± 0.4; 10-Å phase: K298 = 32.2 ± 5.5 GPa, K′ = 9.2 ± 2.8; Phase A: K298 = 145 ± 5 GPa (assuming that K′ = 4). Combining the new talc data with existing thermodynamic data provides a more accurate thermodynamic description of talc than previously available, enabling its high-pressure, high-temperature phase relations to be calculated. The data for 10-Å phase are consistent with a positive slope for its dehydration reaction, making 10-Å phase a good candidate for H2O storage in subducting slabs. The measurements of the thermal expansivity and compressibility of phase A allow its enthalpy of formation and entropy to be derived from the results of phase equilibrium experiments on phase A.